The impacts of urban design on community well-being with the smart city integration - bdullah, Intan Nazuha; Kim Wing, Alan Chong; Chin Tiong, Cheng; Ahmad Karim, Nur Amalina (2023)
The primary purpose of this paper is to discuss the impact of urban design on community wellbeing and the integration of smart cities to emphasise long-term community planning. A comprehensive literature search was conducted to identify publications addressing smart city integration’s effects on community well-being concerning urban design. SpringerLink, ScienceDirect, Google Scholar, and ScienceDirect were accessed for relevant information, and fifty publications were evaluated in total. The publications contain various kinds of literature on the impacts of urban design on community well-being with smart city integration. The period of the review is from 2019 to 2023. After a thorough review, we will filter out literature with redundancy and deemed unsuitable. The findings revealed that community well-being focuses on urban people’s overall quality of life. In contrast, urban design emphasises urban areas’ physical layout and organisation to increase livability, and smart cities use technology to improve urban services and sustainability. Through a rigorous, comprehensive review, this study depicts the impact of urban design on community well-being and the integration of smart cities to emphasise long-term community planning. This study offers several components used in community well-being, the impact of urban design and the integration of smart cities in the community. To the best of the author’s knowledge, little effort has been devoted to the impact of urban design on community well-being with the smart city integration. This research helps to close the gap.